Understanding Environmental Consequences of Quarry Operations: Residents' Perception Study in the Neighbourhood of a Quarry in Osun state, Nigeria - Temitope M Taiwo; Timothy O Ogunbode (SAGE Publishing, 2024)
Investigation on human perspective on the impacts of quarry activities on the natural environment remains limited. This study gauged residents' perceptions of the ecological consequences of quarry operations. A meticulously structured questionnaire was dispensed among 214 households, chosen at random, in the vicinity of Sanlong Quarry within Obaagun community, Ifelodun Local Government Area, Osun State, Nigeria. The dataset underwent analysis utilising both descriptive and inferential statistics. Results indicated a predominance of female respondents, constituting 77.6%, with 65% aged 41 years and above. Moreover, 74.2% had been residents in the study area for no less than 7 years, and 62.6% resided within 1 km of the quarry site. A substantial 74.3% (159 residents) regarded quarry operations as detrimental to their environment, with 72.2% attributing this to machine vibrations. Kaiser-Meyer-Olkins and Barttlet's tests affirmed the factorability of the dataset at a 77.5% significance level ( P  < .005). Factor analysis revealed 7 variables, encompassing 79.19% of residents' perceptions of the environmental impact of quarry operations. These variables included the loss of farmlands (21.35%), degraded farmland (15.06%), vibrations from heavy machines affecting buildings (10.64%), flyrock debris from rock blasting damaging roofs, and the destruction caused by trucks and heavy machinery on rural roads (8.57%). Additionally, wildlife displacement (8.33%) and respondents' perception of the quarry's duration of operation (8.00%) were identified. These findings suggest that quarry operations exert a significant influence on the livelihood of the Sanlong quarry neighbourhood. It is imperative for stakeholders to address this situation through relevant policies, particularly those that enhance the well-being of the community and hold the quarry company responsible for the damages inflicted on various environmental resources. Nonetheless, further study is recommended to validate or otherwise the current findings.